(untitled) (Jurnal Ekonomi Pembangunan Widya Mandira, 2026)
This study analyzes the effect of health quality on education level and labor market efficiency in Indonesia by positioning education as a mediator and the Western–Eastern regional dummy as a moderator. A quantitative approach was applied using panel data from 34 Indonesian provinces during 2021–2024, resulting in 136 observations. The data were analyzed using Partial Least Squares Structural Equation Modeling. Health quality was measured by life expectancy based on the SP2020 LF method, improved drinking water access, and adjusted stunting prevalence. Education level was measured by mean years of schooling and higher education enrollment, while the labor market was measured by the open unemployment rate and labor productivity. The results show that health quality positively affects education but has no direct effect on the labor market. Education positively affects the labor market and fully mediates the effect of health quality. The regional dummy moderates the education–labor market relationship at ? = 10%, with a stronger effect in Western Indonesia